Clube de valentes: empoderamento de meninas por meio da educação - Silva, Alexsandra de Freitas (2022)
The object of research addressed in this dissertation is the educational action of the Brave Club and its contributions to the empowerment of girls. Valentes Club is an educational action that is part of the Dialogical Model of Prevention and Conflict Resolution- MDPRC, developed with young children, starting in early childhood education, and that aims to promote the prevention and overcoming of gender violence in the school space and outside it. The research aimed to identify transforming elements and excluding elements of the Brave Club for the empowerment of girls, from the viewpoint of two teachers and a teacher who develop it in their classrooms in basic education. The methodology used was a qualitative approach, based on the Communicative Methodology, which is based on Habermas' Theory of Communicative Action and Freire's dialogicity. For data collection, the tools used were: communicative interviews/reports and the Communicative Discussion Group. The results of the data analysis showed the excluding elements and the transforming elements of the Brave Club action for the empowerment of girls in the school environment and outside of it. Of the elements that appeared, 15 were transforming elements, elements that potentiate the empowerment of girls and 2 excluding elements, that is, that do not contribute to the empowerment of girls. We conclude with the study that the empowerment of girls, in school spaces, are guaranteed when the children are assured educational actions based on respect, on the promotion of friendship and solidarity, reflections about their actions and making choices. As a success for the development of these actions, the teachers' training appears as fundamental, both the initial training and the continued training of teachers.